Frank Hastings Hamilton papers - Hamilton, Frank Hastings, 1813-1886.
Correspondence, telegrams, memoranda, memorial resolution, military documents, scrapbooks, clippings, and photographs relating to Hamilton's medical career in the Union Army during the Civil War and his role in the treatment of James A. Garfield before his death by assassination in 1881. Also documents Hamilton's postwar work as a surgeon and professor of medicine. Includes military records concerning Colonel Theodore B. Hamilton of the U.S. Army Sixty-second New York Infantry; Confederate army passes and currency; and personal notes and illustrations of a Confederate soldier and a Confederate guerilla.
Physician, surgeon, educator, and author.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Garfield, James A. -- 1831-1881 -- Assassination; Hamilton, Theodore B., -- approximately 1836-1893.; Confederate States of America. -- Army; United States. -- Army -- Surgeons; United States. -- Army. -- New York Infantry Regiment, 62nd (1861-1865); Medical education; Medicine -- Practice; Confederate States of America -- History; New York (State) -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865 -- Medical care; Authors; Educators; Physicians; Surgeons